The effect of the particle shape and structure on the flowability of electrolytic copper powder. III. A model of the surface of a representative particle of flowing copper powder electrodeposited by reversing current - EVICA R. IVANOVIC; LJUBICA J. PAVLOVIC; MILUTIN C. OBRADOVIC; MIOMIR G. PAVLOVIC; SNEZANA B. KRSTIC; KONSTANTIN I. POPOV (Journal of the Serbian Chemical Society, 2004)
The structure of the surface of copper powder particles is discussed and correlated with the lowest apparent density at which copper powder can still flow. It is shown that such structures can be easily obtained in the electrodeposition of powders in reversing current regimes.